2015
DOI: 10.1007/s13126-015-0247-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of n-acetylcysteine and desferoxamine on IL-6, TNF-a, and oxLDL after infrarenal aortic clamping

Abstract: Aim-Background: Treatment of abdominal aortic aneurysms remains a challenging task. We examined the effects of n-acetylcysteine and desferoxamine on interleukin-6, tumour necrosis factor-a, and oxidized low density lipoprotein after infrarenal aortic clamping.Methods: Fifteen piglets were assigned to three groups. The control group (Group C) received saline as placebo (10-mL dilution, bolus), whereas the Group of n-acetylcysteine (Group NAC) received 150mg/kg IV n-acetylcysteine 30 min prior to aortic clamping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…NAC is converted, in vivo, to l-cysteine, which is used in the repletion process of intracellular glutathione [7]. NAC protects against I/R-induced tissue damage due to its ability to scavenge ROS and its anti-inflammatory effects such as suppression of cytokine expression/release, inhibition of adhesion molecule expression and inhibition of nuclear factor kappa B actions [25][26][27][28]. Use of NAC in animal models of I/R injury demonstrated positive results [25,29].…”
Section: N-acetylcysteinementioning
confidence: 99%
“…NAC is converted, in vivo, to l-cysteine, which is used in the repletion process of intracellular glutathione [7]. NAC protects against I/R-induced tissue damage due to its ability to scavenge ROS and its anti-inflammatory effects such as suppression of cytokine expression/release, inhibition of adhesion molecule expression and inhibition of nuclear factor kappa B actions [25][26][27][28]. Use of NAC in animal models of I/R injury demonstrated positive results [25,29].…”
Section: N-acetylcysteinementioning
confidence: 99%
“…In a previous report after generalized ischemia, we indeed also observed that IL-6 was activated very early, whereas IL-1β or tumor necrosis factor-alpha were not [ 27 ]. An increase in IL-6 has been also reported in swine undergoing infra-renal clamping [ 28 ]. Conversely, argon did not significantly modify mRNA blood levels of several cytokines in a previous study in similar conditions, suggesting that argon only reduced reactivity of inflammatory cells through reduced HMGB1 levels but not transcription levels.…”
Section: Discussionmentioning
confidence: 88%
“…After a period of stabilization, supra-coeliac aorta was occluded with a vascular clamp. The occlusion was released after 30 min of aortic cross-clamping, as previously described [ 2 , 28 ]. To optimize hemodynamics, additional administration of saline (10 mL/kg i.v) was performed just after unclamping, followed by a continuous infusion (10 mL/kg/h i.v) until the end of experiment.…”
Section: Methodsmentioning
confidence: 99%